2007
DOI: 10.1056/nejmsa066253
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Number of Medical Conditions and Quality of Care

Abstract: The quality of care, measured according to whether patients were offered recommended services, increases as a patient's number of chronic conditions increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
169
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(193 citation statements)
references
References 30 publications
22
169
1
1
Order By: Relevance
“…Importantly, this association remains robust even when taking into account prior hospitalizations, as well as other indicators of greater patient complexity that could also increase the risk of ACSC-related hospitalization, such as increased age, greater medical comorbidity, poor glucose control and history of alcohol abuse. 32,33 Since hospitalization for an ACSC implies a breakdown in the quality of, and/or access to, primary care, 7,10 our findings suggest that patients with comorbid diabetes and probable major depression may represent a population at particular risk for the declining health status that an ACSC-related hospitalization indicates. 34 Similar to other chronic medical illnesses, diabetes and comorbid mental disorders such as major depression are bidirectionally related.…”
Section: Discussionmentioning
confidence: 81%
“…Importantly, this association remains robust even when taking into account prior hospitalizations, as well as other indicators of greater patient complexity that could also increase the risk of ACSC-related hospitalization, such as increased age, greater medical comorbidity, poor glucose control and history of alcohol abuse. 32,33 Since hospitalization for an ACSC implies a breakdown in the quality of, and/or access to, primary care, 7,10 our findings suggest that patients with comorbid diabetes and probable major depression may represent a population at particular risk for the declining health status that an ACSC-related hospitalization indicates. 34 Similar to other chronic medical illnesses, diabetes and comorbid mental disorders such as major depression are bidirectionally related.…”
Section: Discussionmentioning
confidence: 81%
“…While some studies have found that higher comorbidity burden is associated with better quality of care, 32,33 this relationship is inconsistent 34 and appears to vary substantially depending on a patient's specific conditions and combinations of conditions. 35 Several studies have documented quality of care deficiencies when patients have discordant or unrelated comorbidities.…”
Section: The Relationship Between Multimorbidity and Quality Of Carementioning
confidence: 99%
“…Multimorbid patients tend to have frequent and intensive contact with the health care system, 1,9 resulting in more opportunities to monitor each of their conditions, adjust their treatment regimens, and assess their general health maintenance needs. 32,41 At the same time, each additional condition generates opportunities for suboptimal management, including missed diagnoses, inadequate treatment, and access and communication barriers. If a patient has conditions that are unrelated or discordant, there may be insufficient time or competing demands during a visit, 31,37,42 and the patient and his or her provider may disagree about which condition should be prioritized.…”
Section: The Relationship Between Multimorbidity and Quality Of Carementioning
confidence: 99%
“…These age-related patterns may partly be explained by biographical influences, the differential impact of stress and resilience factors in different age groups, higher proportions of atypical types of depression that are less likely to be identified by the used measures or simply age-related information bias Mauz and Jacobi, 2008;. Also, age-related differences in the use of health care services may influence the prevalence of self-reported diagnosed depression as older people may come into contact with their GP due to other physical complaints (Higashi et al, 2007) and the GP may briefly refer to psychosocial factors (Holvast et al, 2012) thereby providing an opportunity for mental health assessment. Furthermore, older people may be more inclined to report that mental health problems have been discussed (Holvast et al, 2012) and communicate a diagnosis of depression to interviewers.…”
Section: Socio-demographic Correlatesmentioning
confidence: 99%